Compressed matrix core tablet as a quick/slow dual-component delivery system containing ibuprofen - Lopes, Carla Martins (2015)
The purpose of the present research was to produce a quick/slow biphasic delivery system for ibuprofen. A dual-component tablet made of a sustained release tableted core and an immediate release tableted coat was prepared by direct compression. Both the core and the coat contained a model drug ( ibuprofen). The sustained release effect was achieved with a polymer ( hydroxypropyl methylcellulose [ HPMC] or ethylcellulose) to modulate the release of the drug. The in vitro drug release profile from these tablets showed the desired biphasic release behavior: the ibuprofen contained in the fast releasing component was dissolved within 2 minutes, whereas the drug in the core tablet was released at different times (approximate to 16 or 24 hours), depending on the composition of the matrix tablet. Based on the release kinetic parameters calculated, it can be concluded that the HPMC core was suitable for providing a constant and controlled release ( zero order) for a long period of time.